IDENTIFICATION OF MASS MOVEMENT VULNERABILITY ZONES USING STORIE METHOD IN BARUNAI AND SURROUNDING AREAS, LEBAK REGENCY, BANTEN PROVINCE - Hutauruk, Gita Agnes Meilani; Yuningsih, Euis Tintin; Patonah, Aton; Arfiansyah, Kurnia (Faculty of Geological Engineering, Universitas Padjadjaran, 2025)
Natural processes cause mass movement when slope materials, such as soil, rock, and mixed materials, shift from their original positions in a vertical, horizontal, or inclined orientation. A number of factors, including a relatively steep slope, the status of the rock or soil that forms the slope, intense rainfall, unchecked human activity that exploits the environment, and the state of geological structures, contribute to the movement. The research site is located in Cihara District, Lebak Regency, Banten Province, specifically in the Barunai area. Because of their proximity to fault lines and subduction zones, these study areas are susceptible to mass movement, particularly during the wet season. The goal of this study is to pinpoint the regions that are most vulnerable to mass movement. By determining the parameter that is thought to influence mass movement, the Storie method is one technique used to pinpoint the places that are vulnerable to it. The parameters include factors like land usage, type of soil, rainfall, slope, lithology, and geological structures. The research locations are categorized into two levels of mass movement vulnerability based on the analysis result: high, as much as 34.1%, and moderate as much as 65.9%, across the entire research region.